Fermented goat milk as a functional food for obesity prevention or treatment: a narrative review - Andrada, Estefanía; Marquez, Antonela; Russo, Matías; Gauffin-Cano, Paola; Medina, Roxana (Frontiers in Food Science and Technology, 2024)
Fermentation can potentiate goat milk's beneficial properties or generate new bioactive ingredients. In this narrative review, we summarize the current knowledge on the potential of fermented goat milk (FGM) products to improve different biomarkers of a modern epidemic: obesity and its comorbidities. In vitro studies have indicated functional properties of bioactive peptides or lipids obtained from FGM, showing potential to prevent Cardiovascular Disease development and antiinflammatory activity. Probiotic strains derived from goat milk have prevented diet-induced obesity in animal models, and can represent a better techno-functional alternative to ferment this matrix than traditional starters. A small number of studies evaluated the functional properties of FGM in animal models of obesity. The observed in vitro effects of isolated compounds are generally in agreement with in vivo models' findings. Overall, reports showed a positive impact on the prevention of body weight gain and several metabolic, inflammatory, and oxidative parameters. Nevertheless, evidence is limited and the mechanisms involved are fairly unknown. Comparisons between non-fermented and fermented products in in vivo studies are lacking. Functional properties of FGM products aimed at improving the health of obese patients lack support from clinical trials. Considering the current evidence, the administration of complete FGM can be more beneficial to obese patients than the administration of its isolated compounds (lipids, peptides, or microorganisms). The addition of plant by-products with prebiotic or antioxidant properties is a promising strategy to enhance FGM functionality.